Berlin: A hub for startups but not (yet) for fast-growing companies - Alexander S. Kritikos (DIW Economic Bulletin, 2016)
Over the last 20 years, Berlin has developed into Germany's self-employment capital and into a startup hub. A large number ofinnovative companies have been launched.The city has become aninternationally renowned magnet for creative startups. Mainly usingofficial statistical data, the present report shows that the startuptrendin Berlin is above average compared to other major cities inGermany while it is primarily driven by the high startup rates amongnon-Germans. However, with respect to turning startups into fastgrowingcompanies, Berlin has room for improvement. Consequently,future policy measures should focus on supporting these typesof companies. Possible measures include developing high-qualityindustrial sites, cutting red tape and providing fast-track administrativeprocedures in all business-relatedmatters, improving recruitmentprocesses for highly qualified employees, as well as furtherexpanding the knowledge transfer between research institutes andthe fast-growing companies.
Keywords: D22; L26; 330; Start-ups; Entrepreneuship; Berlin